2013
DOI: 10.1161/hypertensionaha.111.00991
|View full text |Cite
|
Sign up to set email alerts
|

Acute Exposure to Diesel Exhaust Impairs Nitric Oxide–Mediated Endothelial Vasomotor Function by Increasing Endothelial Oxidative Stress

Abstract: Abstract-Exposure to diesel exhaust was recently identified as an important cardiovascular risk factor, but whether it impairs nitric oxide (NO)-mediated endothelial function and increases production of reactive oxygen species (ROS) in endothelial cells is not known. We tested these hypotheses in a randomized, controlled, crossover study in healthy male volunteers exposed to ambient and polluted air (n=12). The effects of skin microvascular hyperemic provocative tests, including local heating and iontophoresis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
78
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(84 citation statements)
references
References 46 publications
4
78
1
1
Order By: Relevance
“…NO synthase inhibition with L-NAME decreases the cutaneous heating-induced vasodilation by 20% to 50%, but it reduces the Achinduced hyperemia only by 0% to 15% [27]. This may explain the different time courses of changes in the responses to skin vasodilation in our study, which were significant for the Fasting and Post-fasting session for the less NO-dependent Ach response, but achieved significance during the Fasting only for the more NO-dependent thermal response [37,38].…”
Section: Microvascular Functionmentioning
confidence: 53%
See 1 more Smart Citation
“…NO synthase inhibition with L-NAME decreases the cutaneous heating-induced vasodilation by 20% to 50%, but it reduces the Achinduced hyperemia only by 0% to 15% [27]. This may explain the different time courses of changes in the responses to skin vasodilation in our study, which were significant for the Fasting and Post-fasting session for the less NO-dependent Ach response, but achieved significance during the Fasting only for the more NO-dependent thermal response [37,38].…”
Section: Microvascular Functionmentioning
confidence: 53%
“…Assuming a level of significance at 5% and a study power at 80%, and according to previous validation and interventional studies in our laboratory [26,27], it was estimated that 15 subjects had to participate to demonstrate a threefold increase in the contribution of NO to the microvascular response to heating with fasting. Based on their health status, a total of 27 subjects were considered eligible to participate in the study, among of 60 volunteers.…”
Section: Subjectsmentioning
confidence: 99%
“…Normal human subjects exposed to DEE showed attenuated vasodilatory response to various potent vasodilators (Barath et al, 2010;Mills et al, 2005), indicating a reduction in vasomotor homeostasis that may persist for up to 24 hr post exposure (Tornqvist et al, 2007). The effect was suggested as due to reduced availability of nitric oxide (NO) in the vasculature, postulated, in turn, as due to oxidative stress induced by DEE Wauters et al, 2013). Finally, DEE exposure was found to significantly upregulate vascular endothelial growth factor, which stimulates the migration of monocytes/macrophages, may increase the permeability of the vasculature, and may affect vascular tone (Peretz et al, 2007;Park et al, 2002;Svedas et al, 2003).…”
Section: Cardiovascular Morbidity-human Panel Studiesmentioning
confidence: 99%
“…Previous animal and human studies have demonstrated that acute PM exposure reduces the bioavailability of NO by direct scavenging of NO through reactive oxygen species (ROS) and through impaired endothelial NO synthetase (eNOS), resulting in vasoconstriction (22,23).…”
Section: Antioxidant Pretreatmentmentioning
confidence: 99%